2008
DOI: 10.1348/135910707x250910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (very) brief writing on health: The two‐minute miracle

Abstract: This study tested the lower boundary of the dosage required to garner health benefits from written emotional expression. Participants wrote about either a personal trauma, a positive life experience, or a control topic for 2 minutes each day for 2 days. Emotion word usage in the essays was examined and physical health complaints were measured 4-6 weeks after the last writing session. Trauma and positive experience essays contained more emotional content than the control essays and such content was of a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 16 publications
5
95
0
4
Order By: Relevance
“…Overall, the current findings suggest that PAJ has potential utility as an intervention for managing mental distress, particularly elevated anxiety symptoms, and other aspects of well-being among general medical patients. This is consistent with, and extends, prior research on positive writing interventions as a way to improve aspects of health and well-being [55,69,70,71].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the current findings suggest that PAJ has potential utility as an intervention for managing mental distress, particularly elevated anxiety symptoms, and other aspects of well-being among general medical patients. This is consistent with, and extends, prior research on positive writing interventions as a way to improve aspects of health and well-being [55,69,70,71].…”
Section: Discussionsupporting
confidence: 88%
“…In healthy samples, Armitage and colleagues [54] found beneficial effects of completing a self-affirmation questionnaire or self-affirming implementation intention on alcohol intake at one-month follow-up, while Burton and King [55] observed that participants randomized to write only two minutes for two consecutive days in a lab about a recent positive event showed moderate reductions in physical symptoms (Cohen's d=.65) at 4 to 6-week follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the last intervention, "Optimism," involves a "thinking optimistically" exercise, which prompts users to think about their best possible future scenario and write about it (for well-being benefits, see Burton & King, 2008;Lyubomirsky et al, 2011;Sheldon & Lyubomirsky, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Research has found writing about experiences for just two minutes for two days can bring benefits (Burton and King, 2007). Menary (2007) also suggests that writing is thinking in action, with writing being supported by both manipulations of the external environment and neural processes, such that writing is not just an output of thought, but shapes and enables our thinking.…”
Section: The Human-nature Relationshipmentioning
confidence: 99%